Evaluating the effect of press mud farm manure and synthetic fertilizer alone and in combination under zinc priming on sunflower productivity (Plant Bulletin, 2024)
Sunflower (Helianthus annuus L.) belongs to the family Asteraceae and the genus Helianthus is known as a very important oil crop. The genus Helianthus comprises 65 species and these species are being cultivated for 3000 years. Different biotic and abiotic stress induces negative effects on the growth and development of this crop which in turn reduce productivity. In the present scenario seed priming has diverted the attention of researchers towards it. Seed priming is crucial to enhance crop production by improving growth and development. The current study evaluates the response of organic and inorganic fertilizers on crop yield. The hybrid variety of sunflower (US-666) was studied against different treatments. Different concentrations of synthetic fertilizer, farm yard manure, and sugarcane press mud were used to study the effect on yield compared to control. The maximum value of the number of achene per plant, 1000 grain weight, achene yield per hector, biological yield, and harvesting index was achieved with the application of sugarcane press mud and synthetic fertilizers under the application of zinc 1% solution in the form of priming. But these all yield-related parameters except the biological yield of sunflower reduced to the minimum in the control group (without priming). Split plot design along with statistics 8.1 to evaluate these parameters.
Keywords: Sunflower, Zinc priming, Yield, Press mud, Organic fertilizer